The current status of anatomy knowledge - Yammine, Kaissar (2014)
Background: Gross anatomy is no longer considered a science, as it is no longer considered a research-led discipline. Looking to the current status of anatomical teaching, there is worldwide unanimity regarding the steady decline in the provision of contact hours of this basic science in a crowded undergraduate curriculum. The same could apply at the postgraduate level for specialties where surgical anatomy is essential. The long-term consequence of this shortage of optimal anatomical knowledge is thought to have implications on patient safety. Summary: Where are we now? Anatomy has been, and is still, severely affected by a content and extent reduction policy in most medical schools. Such suboptimal anatomy education has been linked to an increase in some types of medico-legal claims. This could be due in part to the rapid rise of modern learning approaches, lack of gross anatomy teachers, and lack of structured programs. Which direction are we taking, and where do we need to go? The introduction of surface anatomy at the undergraduate level, the implementation of surgical anatomy courses at the postgraduate level, and the revival of dissection courses at both levels could be measures that change the direction of the actual status. How do we get there? (a) The implementation of a national anatomy core curriculum by local medical education societies with a requirement stating the provision of a clinically oriented surface anatomy course. (b) Making room for the time-tested dissection method to be taught in gross anatomy at both levels. (c) The development of explicit and formal teaching in surgical anatomy via postgraduate courses for the concerned specialties. (d) An evaluation of the 3D visualization technology and surgical simulation applied to anatomy teaching. Conclusions: The current suboptimal anatomy knowledge should be acknowledged, and ways to change the course should be searched for. I present my views for possible and practical solutions by introducing surface anatomy at an undergraduate level, implementing surgical anatomy courses at a postgraduate level, and returning to the dissection room at both levels.